Maska Saturna – czyli o smutku w poezjoterapii - Czernianin, Wiktor; Czernianin, Halina (2016)
I. The Mask of Saturn; I. 1. What is sadness ?; I. 2. Melancholy and depression; II. The paths to sadness; II. 1. Pessimism and suffering; II. 2. Illness and death; III. Poetical experience of sadness ; III. 1. The colors of sadness in poetry therapy – the color of the mask of Saturn; III. 1. 1. Components of emotions as determinants of poetic interpretation of sadness; III. 1. 1. 1. Assessment of the situation; III. 1. 1. 2. Changes in the organism; III. 1. 1. 3. Expressing emotions of sadness; III. 1. 1. 4. Motivated action; IV. The End.
Keywords: poetrytherapy; sadness; mask of Saturn; melancholy; pessimism